2003
DOI: 10.1111/j.1525-1438.2003.13362.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal therapy of advanced ovarian cancer: carboplatin and paclitaxel versus cisplatin and paclitaxel (GOG158) and an update on GOG0182-ICON5

Abstract: Mature results from GOG158 have clearly established carboplatin and paclitaxel as an effective and well-tolerated standard regimen, providing a basis for the reference arm in GOG0182-ICON5, an ongoing multiarmed phase III trial of the Gynecologic Cancer InterGroup (GCIG) evaluating the incorporation of newer cytotoxic agents. Results from GOG158 will be reviewed, including an analysis of second-look surgical outcomes, followed by an update on the current status of GOG0182-ICON5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…8,9 A number of retrospective studies and small clinical trials have investigated the role of IP chemotherapy to improve survival as adjuvant treatment of primary EOC. Phase 1 and 2 clinical trials confirmed the feasibility of this method and observed that higher drug concentrations could be reached in the peritoneal space with IP treatment when compared with IV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A number of retrospective studies and small clinical trials have investigated the role of IP chemotherapy to improve survival as adjuvant treatment of primary EOC. Phase 1 and 2 clinical trials confirmed the feasibility of this method and observed that higher drug concentrations could be reached in the peritoneal space with IP treatment when compared with IV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…With more than 60% of the patients presenting the disease in stage III or IV, combination chemotherapy with Platinum and Taxol after cytoreductive surgery gives the most tolerated standard regimen [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…As combination chemotherapy of TP regimen is now established as 'Gold standard' regimen for epithelial ovarian cancer (22,23), the regimen is widely used for all histological sub-types of ovarian tumors. Some reports indicated survival benefit of TP therapy compared with platinum-based chemotherapy in stage I CCC disease combined with complete surgical staging procedures (11) and stage III, IV tumors (9).…”
Section: Discussionmentioning
confidence: 99%